An Integrative Model of Determinants and Moderators of Attitude toward the Brand: Exploring the Mechanisms and Role of Attitude in Brand Marketing (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Marketing has been interested in delving into the mechanisms through which promotional efforts encourage customers to purchase a specific item. in this study we discuss about The Role of Attitude in integrative models, Measuring Self-Image and Brand Personality in the Same Associative Network , Attitude formation and change, Dimensional attitude model, An integrated model of attitude and choice, Levels of interaction, The Relationship between attitude toward the ad and attitude toward the brand , Attitude towards firms’ brand likeability and purchase intention, Brand Extension Strategy, The influence of brand awareness on brand image, The influence of brand awareness on brand trust, Brand commitment